Analytical and Numerical Thermodynamic Equilibrium Simulations of Steam Methane Reforming: A Comparison Study - Bruno Varandas; Miguel Oliveira; Amadeu Borges (Reactions, 2024)
Computer simulation is a crucial element in the design of chemical processes. Although numerous commercial software options are widely recognized, the expense associated with acquiring and sustaining valid software licenses can be prohibitive. In contrast, open-source software, being freely available, provides an opportunity for individuals to study, review, and modify simulation models. This accessibility fosters technology transfer and facilitates knowledge dissemination, benefiting both academic and industrial domains. In this study, a thermodynamic equilibrium steady-state analysis of steam methane reforming using a natural-gas-like intake fuel was conducted. An analytical method was developed on the Microsoft Excel platform, utilizing the material balance equations system. The obtained results were compared to numerical methods employing the free-of-charge chemical process simulation software COCO and DWSIM. The investigation explored the influence of temperature, pressure, and steam-to-carbon ratio to determine optimal operating conditions. The findings suggest that higher temperatures and lower pressures are highly favorable for this process, considering that the choice of steam-to-carbon ratio depends on the desired conversion, with a potential disadvantage of coke formation at lower values. Consistent results were obtained through both analytical and numerical methods. Notably, simulations performed using DWSIM showed a deviation of 6.42% on average compared to COCO values. However, it was observed that the analytical method tended to overestimate the results by an average of 3.01% when compared to the simulated results from COCO, highlighting the limitations of this analytical approach.